PERAN LITERASI KEUANGAN, PROMOSI, DAN RELIGIUSITAS TERHADAP MINAT GENERASI Z PADA BANK SYARIAH DI KABUPATEN KUDUS - Chasan Fauzi, Muchammad; Hasan, Asyari; Lutfi, Mohammad (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2024)
This study aims to determine the influence of Islamic financial literacy, digital promotion, and religiosity in influencing Gen Z's interest in using Islamic banking products in Kudus Regency. The sample in this study used a purposive sampling technique, totaling 170 respondents. The data used is primary data obtained through questionnaires distributed to Gen Z people or prospective customers of Sharia Banks. The data testing in this study uses multiple linear regression. The results of the study found that there was a positive and significant influence of the variables of Islamic financial literacy, digital promotion, and religiosity on the interest in using Islamic banking in Generation Z. Based on a simple regression analysis, it shows that the variables of Islamic financial literacy, digital promotion, and religiosity can affect people's interest in using it. Islamic banking products by 61.8%. This research plays an important role in increasing understanding of Islamic financial literacy, digital promotion, and religiosity in influencing customers' decisions to save in Islamic financial institutions. In addition, this study also emphasizes how important these three factors are in increasing customer interest in choosing to save at a banking institution.